ELEARNING CURRENT SITUATION AND EMERGING CHALLENGES - Bari, Moncef; Djouab, Rachida; Hoa, Chi Phu (PEOPLE: International Journal of Social Sciences, 2018)
This paper aims to present and discuss current, as well as future challenges of eLearning technologies in the higher education institutions and organizations.ELearning has greatly transformed our way of learning by the use of the newly developed technologies and applications. This paper explores the eLearning current situation. After a brief eLearning history, from the earlier 1960’s, with the first generalized computer assisted instruction system PLATO (Programmed Logic for Automatic Teaching Operations) to the 2010's with the development of social media for learning and the MOOC (Massive Open Online Courses). After that, the paper provides a review of the eLearning concept and how it has evolved over the years, followed by a look at the current technologies (from CD-ROMs to Virtual worlds and Game authoring technologies), applications and platforms being used. The emerging challenges are eventually discussed: needs for identifying suitable strategies and understanding the technology and pedagogy integration for effective eLearning implementations referring to pedagogical and cognitive aspects, level of ICT skills for both all the people involved in teaching, total commitment from management for eLearning system operationalization and sustainability, need for software quality frameworks and standards.